EFFECT OF DRUG-METABOLIZING ENZYME ACTIVITY INDUCED BY POLYCHLORINATED BIPHENYL ON THE DURATION OF OXYTETRACYCLINE IN CARP - Djamartumpal F. Lumban Batu (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
A study was made of the induction of drug-metabolizing enzyme activity and the effect of the induced activity on the duration of oxytetracycline (OTC) in carp, Cyprinus carpio. Carp were fed a diet containing polychlorinated biphenyl (PCB)(0,1 mg/100 g body weight/day) for 2 week to induce drug-metabolizing enzymes. After pretreatment, OTC was administered in feed to PCB-treated and control carp as a single dose of 50mg/kg body weight.The result demonstrate that PCB highly induses benzo (a) pyrene hydroxylase among the enzymes of carp, but the induced hydroxylase does not react to OTC, resulting in no change in their tissue levels and duration time.